The legal position of unmarried fathers in the adoption process after Fraser v Children's Court, Pretoria North, and others 1997 (2) SA 261 (CC) : towards a constitutionally-sound adoption statute - SchÃ¤fer, Lawrence Ivan, 1972- (Rhodes University, Faculty of Law, Law, 1999)
The subject-matter of this thesis is the rule, previously contained in section 18(4)(d) of the Child Care Act 74 of 1983, in terms of which a mother could surrender her child born out of wedlock for adoption without the consent of its father. This section was struck down as unconstitutional by the Constitutional Court in Fraser v Children's Court, Pretoria North and others 1997 (2) SA 261 (CC), on the grounds that it violated an unmarried father's constitutional rights to equality and non-discrimination. In the light of this judgment, this thesis seeks to articulate the constitutional parameters within which section 18(4)(d) must be amended. The requirements of Fraser are identified and discussed. Regard is also had to other constitutional rights upon which Fraser might have been decided; in particular, an unmarried father's right to procedural fairness, and his child's right to family or parental care. Case law from the United States, Canada, Ireland and the European Court of Human Rights is also discussed. The end product of this examination is an exposition of the various constitutional rights which vest in the father of a child born out of wedlock. A separate exposition is given of the distinct rights which vest in all children in the adoption process. The latter set of rights is drawn both from the Constitution of the Republic of South Africa Act 96 of 1996, and the United Nations Convention on the Rights of the Child. The thesis then proceeds to examine the Adoption Matters Amendment Act 56 of 1998, which was enacted in response to Fraser. The consent and notice provisions of adoption statutes in the United States, Canada, Australia, Ireland and England are also examined, and compared to the provisions of the Adoption Matters Amendment Act. The object, here, is two-fold: first, to consider the practical value of this Act; and second, to consider whether it satisfies the constitutional requirements identified earlier in this thesis. The thesis concludes with suggestions for the improvement of this Act.
Keywords: Unmarried fathers -- Legal status, laws, etc. -- South Africa; Unmarried fathers -- Legal status, laws, etc. -- Case studies; Children's rights -- South Africa; Adoption -- Law and legislation -- South Africa